Geografia, patrimônio e diversidade cultural: linguagem audiovisual em ações educativas - Gomes, Ana Carolina Rios [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The production and use of images have always been present throughout the history of geographical thought and in anthropological studies. With the advent of new technologies, the use of audiovisual resources for the development and dissemination of knowledge has intensified, often as central to the development of research. At the same time, issues relating to diversity and cultural heritage are evident in cultural policies as well as in academic studies. In this context, the aim of this research is to articulate these aspects, analyzing the potential of the records of cultural practices from the intersections between oral history and Audiovisual Language, implemented in ethnographic documentaries. In addition to empowering communities participating in the production and dissemination of these audiovisual records, recognizing their social importance and narrating his own story, found through an educational action from the reception of documentaries by students in higher education in geography, the produced material has the pedagogical potential in the broad sense, to approach different cultural contexts and promote identity and alterity relations mediated by audiovisual. The ethnographic approach in the classroom indicated that, by capturing attention and emotion, audiovisual language is able to favor the immersion of spectators in life so in fact that records and displays, working the geograficidades and historicity of different communities to contextualize the differences and get along with other ways of being in the world, promoting cultural diversity.

A produção e o uso de imagens sempre estiveram presentes ao longo da história do pensamento geográfico, bem como nos estudos antropológicos. Com o advento de novas tecnologias, a utilização de recursos audiovisuais para a elaboração e difusão de saberes vem se intensificando, muitas vezes como tema central para o desenvolvimento de pesquisas. Ao mesmo tempo, questões relativas à Diversidade e ao Patrimônio Cultural estão em evidência nas políticas culturais e também nos estudos acadêmicos. Diante desse contexto, o objetivo da presente pesquisa é articular essas vertentes, analisando a potencialidade dos registros de práticas culturais a partir das intersecções entre a História Oral e a Linguagem Audiovisual, concretizadas em documentários etnográficos. Além de empoderar comunidades que participam da produção e difusão desses registros audiovisuais, reconhecendo sua importância social e narrando sua própria história, constatamos, por meio de uma ação educativa a partir da recepção de documentários por parte de alunos do ensino superior em Geografia, que o material produzido tem o potencial pedagógico, em sentido lato, de aproximar diferentes contextos culturais e promover relações de identidade e alteridade mediadas pelo audiovisual. A abordagem etnográfica em sala de aula indicou que, por captar atenção e emoção, a linguagem audiovisual é capaz de favorecer a imersão dos espectadores nos modo de vida, na realidade que se registra e se apresenta, trabalhando as geograficidades e historicidades de distintas comunidades para contextualizar as diferenças e conviver com outros modos de ser e estar no mundo, promovendo a diversidade cultural.
Geography, heritage and cultural diversity: audiovisual language in educational actions
Keywords: Cultural geography; Visual anthropology; Oral history; Ethnographic documentaries; Geografia cultural; Antropologia visual; História oral; Documentário etnográfico